Emerging Organic Contaminants in Chinese Surface Water: Identification of Priority Pollutants. (April 2022) - Zhong, Mengmeng; Wang, Tielong; Zhao, Wenxing; Huang, Jun; Wang, Bin; Blaney, Lee; Bu, Qingwei; Yu, Gang
Highlights: Prioritizing 405 EOCs by exposure and hazard potential in Chinese surface water. Hazard potentials were defined using persistence, bioaccumulation, and toxicity. Potential risk to human health or ecological effects was identified for 96 EOCs. The top- and high-priority categories included 11 and 37 compounds, respectively. Environmental quality standards were recommended for 20 EOCs. Abstract: The occurrence and impacts of emerging organic contaminants (EOCs) in the aquatic environment have gained widespread attention over the past two decades. Due to large number of potential contaminants, monitoring campaigns, treatment plants, and proposed regulations should preferentially focus on specific pollutants with the highest potential for ecological and human health effects. In the present study, a multi-criteria screening approach based on hazard and exposure potentials was developed for prioritization of 405 unregulated EOCs already present in Chinese surface water. Hazard potential, exposure potential, and risk quotients for ecological and human health effects were quantitatively analyzed and used to screen contaminants. The hazard potential was defined by contaminant persistence, bioaccumulation, ecotoxicity, and human health effects; similarly, the exposure potential was a function of contaminant concentration and detection frequency. In total, 123 compounds passed the preselection process, which involved a priority index equal to the normalized hazard potential multiplied by the normalized exposure potential. Based on the prioritization scheme, 11 compounds were identified as top-priority, and 37 chemicals were defined as high-priority. The results obtained by the priority index were compared with four other prioritization schemes based on exposure potential, hazard potential, or risk quotients for ecological effects or human health. The priority index effectively captured and integrated the results from the more simplistic prioritization schemes. Based on identified data gaps, four uncertainty categories were classified to recommend: ① regular monitoring, derivation of environmental quality standards, and development of control strategies; ② increased monitoring; ③ fortified hazard assessment; and ④ increased efforts to collect occurrence and toxicity data. Overall, 20 pollutants were recommended as priority EOCs. The prioritized list of contaminants provides the necessary information for authoritative regulations to monitor, control, evaluate, and manage the risks of environmentally-relevant EOCs in Chinese surface water.